PHOTOLUMINESCENCE OF ZnO NANOSTRUCTURE PREPARED BY CATALYST - ASSISTED VAPOR - LIQUID - SOLID TECHNIQUE - Tran Thi Quynh Hoa; Ta Dinh Canh; Nguyen Ngoc Long; Nguyen Viet Tuyen; Nguyen Duy Phuong (ASEAN Journal on Science and Technology for Development, 2007)
ZnO semiconductor nanostructures have been synthesized by thermal evaporation of mixture of ZnO and graphite powders. The thin layer of gold coated on Si substrates was used as a catalyst. The structure analysis shows high crystallinity of ZnO, their preferred orientation along the (0 02) plane of the wurtzite phase and their chemical purity. The scanning electron microscopy (SEM) images of products indicate that ZnO nanowires have a diameter of about 40 - 150 nm and a length of up to tens of micrometers. The morphology and structure of ZnO nanowires and nanorods depend on the thicknesses of the Au layers. The fact that Au nanoparticles are located at the tips of the nanowires represents a strong evidence for a growth process dominated by the vapor - liquid - solid mechanism. The low temperature photoluminescence spectra of the ZnO nanowires indicate a group of the ultraviolet narrow peaks and a blue - green very broad peak at 500 nm.